The maximum volume of hyperbolic polyhedra - Belletti, Giulio (Transactions of the American Mathematical Society, 2021)
We study the supremum of the volume of hyperbolic polyhedra with some fixed combinatorics and with vertices of any kind (real, ideal, or hyperideal). We find that the supremum is always equal to the volume of the rectification of the -skeleton.
Article electronically published on November 3, 2020
Gesehen am 19.02.2021